Effect of superheat degree on the performance of an organic Rankine cycle system that utilizes a wet working fluid - Jui‐C. Hsieh; Yi‐C. Hsieh; Yen‐H. Chen (Energy Science & Engineering)
Abstract Limited experimental research has been conducted on organic Rankine cycle (ORC) systems that use wet working fluids. Therefore, the present study examined how the performance of an ORC system that uses a wet working fluid (R134a) was affected by the superheat degree ratio (SDR) under various scroll rotation speeds. The SDR is the dimensionless ratio between superheat degree and evaporation temperature at a given heat source temperature. Experimental results indicated that at scroll rotation speeds of 900, 1350, and 1800 rpm, the maximum output power of the aforementioned system was 1103, 1464, and 1537 W, respectively, with SDRs of 0.49, 0.49, and 0.54, respectively. The maximum net efficiencies at these speeds were 5.87%, 5.91%, and 5.32%, respectively, which occurred at SDRs of 0.61, 0.49, and 0.48, respectively. This level of system performance was attributable to the high enthalpy at the expander inlet and the high mass flow rate at the high evaporation pressure under an SDR of approximately 0.5. Although increasing the SDR did not enhance the scroll expander's isentropic efficiency, this efficiency decreased considerably when the SDR fell below 0.2. These findings emphasize the importance of optimizing the SDR of ORC systems to improve their performance.